PENANAMAN ANTI RADIKALISME PADA PONDOK PESANTREN ROUDLOTUL MUBTADIIN BALEKAMBANG JEPARA (Sosiolium: Jurnal Pembelajaran IPS, 2023)
Anti-radicalism education in Islamic boarding schools is very necessary, considering the spread of radicalism is now starting to bloom. The understanding of anti-radicalism must be taught from an early age, especially in Islamic boarding schools which are often the goal of spreading the understanding of radicalism. The purpose of understanding anti-radicalism in Islamic boarding schools is as a shield for students to fight radical attitudes. The purpose of this study aims to determine how the attitude of Islamic boarding schools in responding to anti-radicalism in society. The method used is descriptive qualitative method. Sources of data obtained from informants, observations, and documents. Data collection tools and techniques are observation, interviews, and documents. The validity of the data was tested by triangulation technique. Data analysis techniques through data collection, data reduction, data presentation, as well as drawing conclusions and verification. The results of the study show that (1) the ability of educators to provide teaching in anti-radical attitudes (2) the media often used by educators/ustadz in implementing anti-radicalism attitudes are quite relevant (3) Obstacles that are often felt by educators when implementing anti-radical attitudes learning radicalism in Islamic boarding schools. Pendidikan anti radikalisme di pondok pesantren sangat diperlukan, mengingat persebaran paham radikalisme sekarang sudah mulai marak teradi. Pemahaman anti radikalisme harus mulai diajarkan sejak dini, terutama di pondok pesantren yang sering juga menjadi tujuan penyebaran pemahaman radikalisme. Tujuan penelitian ini bertujuan untuk mengetahui bagaimana sikap pondok pesantren dalam menyikapi paham anti radikalisme di masyarakat. Metode yang digunakan berupa metode kualitatif deskriptif. Sumber data diperoleh dari informan, hasil pengamatan, dan dokumen. Alat dan teknik pengumpulan data adalah, observasi, wawancara, dan dokumen. Keabsahan data diuji dengan teknik triangulasi. Teknik analisis data melalui pengumpulan data, reduksi data, penyajian data, serta penarikan kesimpulan dan verifikasi. Hasil penelitian menunjukkan bahwa (1) kemampuan pengampu dalam memberikan pengajaran dalam bersikap anti radikal (2) media yang sering digunakan oleh pengampu/ustadz dalam melaksanakan penanaman sikap anti radikalisme yang cukup relevan (3) Kendala yang sering dirasakan oleh pengampu saat pelaksanaan pembelajaran sikap anti radikalisme di pondok pesantren.